Activity of inhibit the cell cycle and induct apoptosis in HeLa cancer cell with combination of Sabrang onion (Eleutherine palmifolia (L.) Merr) and Starfruit Mistletoe (Macrosolen cochinchinensis (Lour.) Tiegh) - Roihatul Mutiah, Anik Listiyana, Arief Suryadinata, Rahmi Annisa, Abdul Hakim, Wirda Anggraini, Retno Susilowati (Journal of Applied Pharmaceutical Science, 2018)
The combination of Eleutherine palmifolia (L.) Merr (EP) and Macrosolen cochinchinensis (Lour.) Tiegh (MC) extracts has been proven an empirically potential cure for cancer. The aims of this research were to prove scientifically the anticancer potential of the combination of EP and MC as well as its effects on the cell cycle and the apoptosis of HeLa cancer cell. The MTT method was used to measure cytotoxic effects. The effect of inhibition of cell cycle and induction of cell apoptosis was measured by the flow cytometry method. The results showed that the combination of EP and MC gives an induction of apoptosis effect of HeLa cancer cell through inhibition of cell cycle in the G0-G1, S, and G2/M phases synergistically until it is synergist strong. Therefore, the combination of EP and MC can be recommended as a candidate drug for cancer therapy.
Keywords: Eleutherine palmifolia (L.) Merr, Macrosolen cochinchinensis (Lour.) Tiegh, anti-cancer, HeLa cervical cancer cell.